2016
DOI: 10.1095/biolreprod.115.130369
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cnnm1 and Its Association with Stemness, Cell Cycle, and Differentiation in Spermatogenic Cells in Mouse Testis

Abstract: Cyclin M1 (CNNM1) functions as a copper storage protein in neuronal cells. We report that Cnnm1 is expressed in mouse testis and brain and has a coding sequence of 1761 bp that encodes a 586 amino acid protein with a molecular weight of 66 kDa. Cnnm1 is expressed in the testes of mice from neonatal to adult stages with relatively higher levels in neonates. CNNM1 expression appeared to be restricted to c-KIT- and OCT3/4-positive cells in the testis, indicating that they are early spermatogonial cells. Spermatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…GC-1spg cells, a mouse spermatogonia-derived cell line, represent the differentiation state of type B spermatogonia or preleptotene spermatocytes [1,37]. Several studies have demonstrated GC-1spg cell plasticity [1,4,78,79]. In our study, we drove BMP9 expression using a recombinant adenovirus.…”
Section: Discussionmentioning
confidence: 99%
“…GC-1spg cells, a mouse spermatogonia-derived cell line, represent the differentiation state of type B spermatogonia or preleptotene spermatocytes [1,37]. Several studies have demonstrated GC-1spg cell plasticity [1,4,78,79]. In our study, we drove BMP9 expression using a recombinant adenovirus.…”
Section: Discussionmentioning
confidence: 99%
“…Also known as OGA, MGEA5 influences folliculogenesis [73]. Expression of Cnnm1 (cyclin M1) is associated with cell cycle and differentiation in spermatogenic cells in mouse testis [74]. Chd5 expression is restricted to post-meiotic spermatids [75].…”
Section: Several Candidate Icr Map To the Vicinity Of Genes Encoding mentioning
confidence: 99%
“…POU3F1 is involved in survival and self-renewal of mouse spermatogonial stem cells [72]. CNNM1 is produced in mouse testes from neonatal to adult stages [74]. CHD5 mediates histoneto-protamine replacement and impacts the cascade of molecular events underlying chromatin remodeling during spermatogenesis [75].…”
Section: Several Of the Candidate Icrs Map To Genes With Functions Ramentioning
confidence: 99%
See 1 more Smart Citation
“…It is a cell type that intermediates between type B spermatogonia and pre‐leptotene spermatocyte. It exhibited some characteristics of early spermatogonia which did not express STRA8 but could be induced to express STRA8 by RA . The HEK‐239T cell line (Human embryonic kidney cells, lentivirus‐mediated overexpressed STRA8‐GC1 spg (SGC1) and its control GC1 spg (CGC1) were derived in our laboratory.…”
Section: Methodsmentioning
confidence: 99%